Notaries' signs and drawings: first assessments of Genoese documentation (12th-13th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The paper aims to be a first and very preliminary approach to the complex topic of the graphic ability expressed by the Genoese notaries, especially in relation to the presence of figurative elaborations, free drawings or influenced ones, within the documnetary production of the category, following up what emerged in other Italian territorial realities, including neighboring ones.
Keywords: Notarial Protocols; Notarial signa; Genoa commune; 12th-13th Centuries; Medieval Graphic Design